Characterisation of bismuth-based erbium-doped fibre and its application in wide-band optical amplifiers / Nizam Tamchek. - Tamchek, Nizam (2009)

(untitled)
In this thesis, the characterisation of Bismuth based Erbium-doped Fibre Amplifier (Bi-EDFA) for Conventional- and Long- (C+L) Wide-band optical amplifier in Wavelength Division Multiplexing (WDM) optical network was presented and performed. Bismuth based Erbium-doped Fibre is a novel optical gain material that was specifically developed for current and future optical amplifiers. The work focuses on the optical amplifier's characteristic and performance of Bi-EDFA using bi-directional pumping configuration as a potential optical amplifier for 1.55 μm optical communication. The material, physical and optical characteristics of Bi-EDF are calculated, measured and successfully demonstrated the necessary properties for efficient optical amplifier but also highlight the problem associated with higher Erbium ions dopant concentration and Bismuth host glasses. In addition, the effect of self-saturation was investigated and found to influence the gain, noise and efficiencies of the output signal. These important knowledge then discussed for development and prospect of Bi-EDFA as potential optical amplifier in future optical communication system.